A fuzzy model for evaluating risk impacts on variability between contract sum and final account in government-funded construction projects. Issue 1 (2nd February 2015) - Ameyaw, Ernest Effah; Chan, Albert P.C.; Owusu-Manu, De-Graft; Coleman, Ekow
Abstract : Purpose: – The purpose of this paper is to identify and then evaluate perceived risk factors influencing variability between contract sum and final count, and to develop a fuzzy risk assessment model for evaluating the overall impact of established critical risk factors impacting on variability between contract sum and final account in government-funded construction projects. Construction projects are characterised by risk factors that significantly impact on variability between the contract sum and final account. Design/methodology/approach: – A research approach integrating questionnaire survey, mean scoring ranking and principal component factor analysis (PCFA) methods was adopted to evaluate and classify the critical risk factors. A fuzzy synthetic evaluation method was sequentially applied to compute the overall risk impact (ORI) of eight critical risk factors' impact on variability between contract sum and final account. Findings: – Initial results showed that eight critical risk factors have high impact on variations between contract sum and final account, namely (in order): project funding problems, underestimation of quantities, variations by client, change in scope of works, inadequate specification, change in design by client, defects in design and unexpected site (ground) conditions. PCFA produced two factor solutions: "professional-related factors" and "client factors". The fuzzy model further showed that the ORI is 5.48, indicating that these risk factors have a high impact on variability between contract sum and final account in public construction projects. The client factors have a very high impact (5.59), while the professional-related factors indicated a high impact (5.41) on project cost variability. Originality/value: – A practical model is proposed to evaluate the key risks associated with cost overruns in public projects. By giving effective and sustained attention to these factors, variability between contract sum and final account, a common situation in Ghana, can be controlled to achieve cost savings in public infrastructure projects.